Growth performance and carcass characteristics of crossbred finishing pigs fed diets rich in palm oil (Orinoquia, 2022)
The sabanero pig, a Creole breed from Colombia present in the Orinoquia, is a local genotype with several advantages, such as high adaptation to local environmental conditions and abundance in several states of the region. Factors that would suggest a huge potential for increase the productivity and efficiency of the local pig industry.  However, little has been explored about the contribution that this breed would bring to commercial breeds on the basis of its rusticity and adaptability. The objective of this study was to evaluate the growth performance and carcass quality of crossbred pigs (Sabanero x commercial) at fattening (20 to 90 kg) compared to commercial breeds.  The pigs were fed whit a high fatty acids diet, using crude palm oil as the main source of energy. Productive parameters such as weight gain and feed conversion were evaluated, as well as some carcass characteristics (yield, loin eye diameter and backfat thickness). No significant differences were found in growth parameters, crossbred pigs recorded an average daily gain of 522 g, while commercial pigs reached 524 g, regardless of the breed group, feed intake was 1.3 kg and feed conversion was 2.5. Carcass characteristics such as backfat thickness (23 and 21.47 mm) or loin eye diameter (8 and 10.07 cm) were also not influenced by breed group, however, carcass yield was higher (P < 0.05) for commercial pigs when compared to crossbred Sabanero pigs (71.54 and 76.17%). The Sabanero pigs breed crossed with commercial lines could be a viable productive alternative, which would allow their sustainable use and conservation. Future research is needed to determine the effects of this crossbreeding on meat quality, with the possibility of generating products with a differentiated value to compensate for the lower carcass yield.
Keywords: creole pig; zootechnical parameters; performance; local resources